Building codes illustrated for healthcare facilities : - Winkel, Steven R. (John Wiley, 2007)
Now more than ever, architects need an interpretive guide to understand how the building code affects the early design of specific projects. This easy-to-use, illustrative guide is part of a new series covering building codes based on the International Building Code for 2006. This book presents the complex code issues inherent to healthcare facility design in a clear, easily understandable format.